What about Social Vulnerability in Colombia? Connecting “freedom from” and “freedom to” - Lampis, Andrea (Sociedad y Economía, 2010)
This paper has two main objectives, both related to an interest in counteracting the domination of income-centred approaches to poverty in Colombia. The first is to reconstruct the historical and conceptual steps of the research stream that developed a reflection on assets, livelihoods and vulnerability. The second, to present the results of a case study carried out in 2006/7 in Bogotá, Cali and Manizales as far as the case of the Colombian capital is concerned. The analysis illustrates the relevance of a vulnerability approach to identify a connection between “freedom from” (critical life events) as a necessary element to achieve “freedom to” (improve people´s capabilities).